Rethinking Pyogenic Flexor Tenosynovitis: Biofilm Formation Treated in a Cadaveric Model - Ketonis, Constantinos; Hickock, Noreen J.; Ilyas, Asif M. (Journal of Hand and Microsurgery, 2017)
Introduction Pyogenic flexor tenosynovitis (PFT) of the hand remains a challenging problem that often requires surgical irrigation and parenteral or oral antibiotics. The authors hypothesize that the pathophysiology and microenvironment of PFT can be likened to that of periprosthetic joint infections (PJIs), in which bacteria thrive in a closed synovial space with limited blood supply. As such, they postulate that PFT is also facilitated by bacterial attachment and biofilm formation rendering standard treatments less effective. In this study, they evaluate infected tendons for the presence of biofilm and explore new treatment strategies.Methods Fresh human cadaveric hand tendons were harvested and divided into 0.5-cm segments. Samples were sterilized and inoculated with 1 × 104 CFU/mL green fluorescent Staphylococcus aureus (GFP-SA) for 48 hours at 37°C. After saline washing to remove plank tonic bacteria, samples were treated for 24 hours with (1) saline irrigation, (2) antibiotics (vancomycin), (3) corticosteroids, or (4) antibiotics/corticosteroid combined. Samples were visualized using confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM).Results Following bacterial challenge, CLSM revealed heterogeneous green fluorescence representing bacterial attachment with dense biofilm formation. SEM at > 3,000X, also demonstrated bacterial colonization in grape-like clusters consisted with a thick matrix characteristic of biofilm. Bacterial load by direct colony counting decreased by 18.5% with saline irrigation alone, 42.6% with steroids, 54.4% with antibiotics, and 77.3% with antibiotics/steroids combined (p < 0.05).Conclusion Staphylococcus aureus readily formed thick biofilm on human cadaveric tendons. The addition of both local antibiotics and corticosteroids resulted in greater decreases in biofilm formation on flexor tendons than the traditional treatment of saline irrigation alone. We suggest rethinking the current treatment of PFT and recommend considering a strategy more analogous to PJI management with the adjunctive use of local antibiotics, corticosteroids, and mechanical agitation.
Keywords: pyogenic; septic; suppurative; flexor tenosynovitis; biofilm